2011
DOI: 10.1371/journal.pgen.1001264
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing and Comparative Transcriptomics of the Model Entomopathogenic Fungi Metarhizium anisopliae and M. acridum

Abstract: Metarhizium spp. are being used as environmentally friendly alternatives to chemical insecticides, as model systems for studying insect-fungus interactions, and as a resource of genes for biotechnology. We present a comparative analysis of the genome sequences of the broad-spectrum insect pathogen Metarhizium anisopliae and the acridid-specific M. acridum. Whole-genome analyses indicate that the genome structures of these two species are highly syntenic and suggest that the genus Metarhizium evolved from plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
618
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 561 publications
(646 citation statements)
references
References 126 publications
18
618
0
3
Order By: Relevance
“…Dtxs are recognized as important virulence determinants in Metarhizium spp (11)(12)(13). The Metarhizium genus contains a dozen species (14), including M. anisopliae and M. robertsii, which can kill hundreds of insect species, and M. acridum, which can only kill locusts and grasshoppers (15,16). It has frequently been observed that dtx production correlates with host specificity (12,17).…”
mentioning
confidence: 99%
“…Dtxs are recognized as important virulence determinants in Metarhizium spp (11)(12)(13). The Metarhizium genus contains a dozen species (14), including M. anisopliae and M. robertsii, which can kill hundreds of insect species, and M. acridum, which can only kill locusts and grasshoppers (15,16). It has frequently been observed that dtx production correlates with host specificity (12,17).…”
mentioning
confidence: 99%
“…The RASP yielding ancestral lifestyle and the identification of numerous plant parasitism-related genes in the genomes of Metarhizium spp. also support this hypothesis (Gao et al 2011). …”
Section: Discussionmentioning
confidence: 55%
“…The utilisation of host-based nutrition is critical for fungal parasitism and includes or carbohydrate-activated enzymes (CAZymes) and as well as proteases, which are among key virulence factors involved in parasitism in various pathogenic fungi (Gao et al 2011; Klosterman et al 2011; Xiao et al 2012). The abundance and types of these enzymes should be key to the adaption to different host-based nutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the proteins in the oxidoreduction-driven transporter subclass are expanded (Supplementary Table 18, Supplementary Note 7). Many MFS transporters are involved in the transport of a wide range of nutrient substrates, such as sucrose, galactoside, amino acid and peptides 34 . Reduced MFS transporters and lack of Comparison between the putative PKS gene cluster for ustilaginoidin biosynthesis in U. virens (upper) and the aurofusarin biosynthesis gene cluster in F. graminearum (bottom).…”
Section: Resultsmentioning
confidence: 99%